Employment protection legislation. Evolution, effects, winners and losers - Skedinger, Per (Cheltenham, 2010)
"Employment protection legislation is one of the most controversial issues in the labour market. In this insightful book, Per Skedinger provides an overview of the design, evolution and research on the effects of employment protection legislation around the world. Most countries have some form of employment protection legislation. Against a background of high and rising unemployment in many countries, politicians and representatives of unions and businesses often have differing views as to the desirability, effects and distributional consequences of the legislation. The book covers more than one hundred international studies, dealing with the impact of legislation on productivity, personnel turnover, structural change, perceived job security, and the aggregate level and distribution of employment and unemployment. Being the first comprehensive and up-to-date survey available of economic research on the effects of employment protection, this book will appeal to researchers in economics, industrial relations and law, as well as to policymakers and practitioners dealing with employment protection issues in government, business and trade unions."